Phenethyl isothiocyanate suppresses cancer stem cell properties in vitro and in a xenograft model - Yun, Ji Ho; Kim, Kyung-A; Yoo, Gyhye; Kim, Sun Young; Shin, Ji Min; Kim, Jung Hoon; Jung, Sang Hoon; Kim, Jungho; Nho, Chu Won (ELSEVIER GMBH, URBAN & FISCHER VERLAG, 2017)
Background: Cancer stem cells (CSCs) are a subset of cells within the bulk of a tumor that have the ability to self-renew and differentiate, and are thus associated with cancer invasion, metastasis, and recurrence. Phenethyl isothiocyanate (PEITC) is a natural compound found in cruciferous vegetables such as broccoli and is used as a cancer chemopreventive agent; however, its effects on CSCs are little known. Purpose: To evaluate the effect of PEITC on CSCs in this study by examining CSC properties. Methods: NCCIT human embryonic carcinoma cells were treated with PEITC, and the expression of pluripotency factors Oct4, Sox-2, and Nanog were evaluated by luciferase assay and western blot. Effect of PEITC on self-renewal capacity and clonogenicity were assessed with the sphere formation, soft agar assay, and clonogenic assay in an epithelial cell adhesion molecule (EpCAM)-expressing CSC model derived from HCT116 colon cancer cells using a cell sorting system. The effect of PEITC was also investigated in a mouse xenograft model obtained by injecting nude mice with EpCAM-expressing cells. Results: We found that PEITC treatment suppressed expression of the all three pluripotency factors in the NCCIT cells, in which pluripotency factors are highly expressed. Moreover, PEITC suppressed the self-renewal capacity and clonogenicity in the EpCAM-expressing CSC model. EpCAM was used as a specific CSC marker in this study. Importantly, PEITC markedly suppressed both tumor growth and expression of three pluripotency factors in a mouse xenograft model. Conclusion: These results demonstrate that PEITC might be able to slow down or prevent cancer recurrence by suppressing CSC stemness. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: SIGNALING PATHWAY; DRUG-RESISTANCE; GENE-EXPRESSION; EPCAM; OCT4; CHEMOPREVENTION; SULFORAPHANE; INHIBITION; ACTIVATION; MECHANISMS